The derivative of
can be found using the product rule of differentiation.
Step-by-step explanation:
The derivative of
can be found using the product rule of differentiation. The product rule states that the derivative of the product of two functions, u and v, is given by the formula (u*v)' = u'v + uv'.
Let
and
. Taking the derivatives of u and v, we have:
![u' = 3x^2v' = 2e^{(2x)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2cd5a9mnhxdhzk5zmfuphqm47zvh4bnojb.png)
Using the product rule, the derivative of x^3e^{(2x) is:
![(x^3e^((2x)))' = u'v + uv' = (3x^2)(e^((2x))) + (x^3)(2e^((2x))) = 3x^2e^((2x)) + 2x^3e^((2x))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/y69n3c571aefjxtrpb2b87ewloo81o8zx6.png)